DEVELOPMENT OF A MOBILE-BASED ECOTOURISM GUIDE APPLICATION FOR TANDUNG BILLA USING GEOFENCE AND AUGMENTED REALITY TECHNOLOGY - Dianradika Prasti; Rusdi, Muhammad Idham (Jurnal INSTEK (Informatika Sains dan Teknologi), 2025)
This study aims to develop a mobile-based ecotourism guide application for Tandung Billa, utilizing Geofence and Augmented Reality (AR) technologies. The application is designed to automatically provide contextual information when tourists are at specific locations using the Geofence feature. Additionally, AR technology is employed to display virtual objects and information about ecotourism spots such as the Nursery Ticket Booth, Apiculture Area, Hall, Bamba Butterfly Park, and Camping Ground. The development process follows the Multimedia Development Life Cycle (MDLC) method. System testing was conducted using the Black Box technique. Expert evaluations were also carried out through application validation. To assess the application's suitability for user needs, a user response test was conducted. The results of the black box testing indicated successful outcomes, meaning all application interfaces functioned properly. Expert evaluations, involving three specialists in the field, yielded an average score of 98%, indicating that the application is highly feasible for use. Furthermore, the user evaluation involving 10 respondents resulted in a score of 95, categorized as highly feasible, confirming that the application is suitable for field implementation.